Atomic‐Level Metal Electrodeposition: Synthetic Strategies, Applications, and Catalytic Mechanism in Electrochemical Energy Conversion. Issue 3 (10th March 2022) - Shi, Yi; Lee, Carmen; Tan, Xianyi; Yang, Lan; Zhu, Qiang; Loh, Xianjun; Xu, Jianwei; Yan, Qingyu
Abstract : Atomic‐Level Metal Electrodeposition Electrodeposition enables a fast, mild, and controllable growth of metal catalysts at an atomic level. In article number 2100185, Jianwei Xu, Qingyu Yan, and co‐workers summarize the recent developments of atomic‐level metal electrodeposition in terms of basic principles, synthetic strategies, applications, and catalytic mechanism in electrochemical energy conversion.